Rewrite without parentheses and simplify. (w+6)^2?

learning new mathematics equations

7 Answers

Relevance
  • 5 months ago

    (w + 6)^2 = w^2 + 12w + 36

  • 5 months ago

    (w + 6)^2

    = w^2 + 12w + 36

  • David
    Lv 7
    5 months ago

    It is: w^2 + 12w + 36 = (w+6)^2

  • TomV
    Lv 7
    5 months ago

    (w+6)² = (w+6)(w+6)

    = w(w+6) + 6(w+6)

    = w² + 6w + 6w + 36

    = w² + 12w + 36

    Commit to memory the relationship (a+b)² = a² + 2ab + b²

    (w+6)² = (w)² + 2(w)(6) + (6)²

    = w² + 12w + 36

  • What do you think of the answers? You can sign in to give your opinion on the answer.
  • 5 months ago

    w^2 + 12w + 36

    (x + y)^2 = x^2 + 2xy + y^2

  • 5 months ago

    w^2 + 6w + 6w +36 =

    w^2 + 12w + 36

  • Mike G
    Lv 7
    5 months ago

    w^2+12w+36

    .................

Still have questions? Get answers by asking now.